(untitled) (Al-Muwazanah: Indonesian Journal of Islamic Economics, 2025)
Moral obligation in paying taxes is an important aspect that is not only related to legal provisions but also encompasses profound ethical and philosophical dimensions, especially in the context of justice and universal duty according to Immanuel Kant’s perspective. Kant’s philosophical approach emphasizes that moral actions should be based on universal principles and respect for human rights, so paying taxes is not merely a legal obligation but a moral act that reinforces social justice and respects individual rights. The positive impact of applying this principle is the creation of a fair and transparent taxation system, which can encourage society to contribute voluntarily for the common welfare, and strengthen trust and social responsibility. However, on the other hand, negative effects such as dishonesty and corruption in tax management can lead to trust issues within society and diminish their moral sense in fulfilling tax obligations. The aim of this research is to philosophically examine how Kant’s principles of justice and universal duty can be applied within the context of taxation, and to analyze their impact on social and moral systems in society. The research questions include how Kant’s views on moral obligation can reinforce collective awareness in paying taxes and how the taxation system can be optimized to align with these moral principles. The research method employed is a literature review with a qualitative approach, collecting data from Kant’s works, moral philosophy literature, and related studies on tax practices. The findings indicate that applying Kant’s moral principles can strengthen the legitimacy of the moral and social obligation to pay taxes, but its effectiveness heavily depends on the integrity of management and transparency within the taxation system, so that public trust remains maintained and social justice can be realized optimally